Dissimilaridade entre porta-enxertos para pessegueiros Chimarrita e Maciel em diferentes locais de cultivo - Galarça, Simone Padilha (2012)
Objectified with this work to assess the nutritional aspects, phenological, vegetative plants mortatidade, yield and quality of the fruit of cultivars Maciel and Chimarrita on different rootstocks on three growing locations in Rio Grande do Sul. The experiment was conducted in three locations: 1 location: Experimental Station of Embrapa Uva e Vinho, location 2: Agricultural Experimental Station of the Federal University of Rio Grande do Sul and local 3: Agricultural Centre of Palma da Universidade Federal de Pelotas in the years 2009, 2010 and 2011. Were evaluated variables relating to nutrition of peach, full bloom and flowering period, growth and mortality of plants, yield and quality of fruit. The results obtained showed that regardless of place of cultivation of peach rootstocks, interfered in the characteristics of the peaches of cultivars Maciel and Chimarrita. The rootstocks affected the nutrient vegetative growth, flowering plants, mortality and quality of fruit. The nutrients most affected to the peach Chimarrita were the calcium, magnesium and iron; and for the peach Maciel were the magnesium and manganese. The force of peach Chimarrita and Maciel is less about the graft-Umezeiro. This divergence is defined largely by the variables trunk diameter, Cup fresh volume and mass withdrawal of pruning. The rootstock Okinawa and Capdeboscq are sensitive to poorly drained soils and the graft-Umezeiro the replanting areas. The components of quality of fruit were most affected by rootstocks in 2 locations (EEA UFRGS) and 3 (CAP UFPel). The graft-Umezeiro is not recommended for the location 2 (EEA UFRGS), combined with peach Chimarrita due to lack of production 2009 and 2010 but is recommended for the location 3 (CAP UFPel) combined with the peach Maciel because of the productive efficiency and Ratio SS/AT larger. Other graft can be used in all three places of cultivation.